PEMAHAMAN IBU DALAM PENCEGAHAN STUNTING PADA ANAK BALITA DI DESA LOBOAJU, KECAMATAN SABU TENGAH, KABUPATEN SABU RAIJUA - Bire, Florida Bangngu; Makleat, Nirwaning; Mardani, Ambara Saraswati (Universitas Nusa Cendana, 2024)
ABSTRACK Stunting is a condition of failure to thrive caused by chronic malnutrition, especially in the first thousand days of life (HPK). this research aims to find out mothers' understanding of preventing stunting in children under five. The method used in this research is qualitative research with a case study approach to explore the phenomenon of stunting problems in children under five. The techniques used to collect data are observation, interviews and documentation. The number of informants in this study was five (5) people aged 20-40 years who had stunted children under five. The research results show that in the literacy section, informants understand that exclusive breastfeeding is important, but in reality not all informants can provide exclusive breastfeeding because there are various factors, including the mother's physical condition which does not allow her to produce a lot of breast milk and mothers who have to work to earn a living. Then in terms of education, the informant also knew that providing nutritious food was also important, but in reality the food menu given was always the same, making children bored and having difficulty eating, which could result in unbalanced nutritional problems. Furthermore, regarding environmental sanitation, mothers let children play around the house without supervision so that children's cleanliness is given less attention. The behavior of providing immunization is good because all toddlers have been fully immunized and economic planning practices are not implemented because economic conditions do not allow it.